2021
DOI: 10.1017/jfm.2021.579
|View full text |Cite
|
Sign up to set email alerts
|

Wettability and Lenormand's diagram

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 84 publications
1
63
0
Order By: Relevance
“…It was also interesting to find that the experimental observations were consistent with the results by the modified network models (Primkulov et al. 2018, 2019, 2021), which indicated that the critical wettability for best displacement generally corresponded to the cooperative pore-filling mode.…”
Section: Introductionsupporting
confidence: 71%
“…It was also interesting to find that the experimental observations were consistent with the results by the modified network models (Primkulov et al. 2018, 2019, 2021), which indicated that the critical wettability for best displacement generally corresponded to the cooperative pore-filling mode.…”
Section: Introductionsupporting
confidence: 71%
“…2017; Primkulov et al. 2018, 2019, 2021). As the solid becomes more wetting to the invading fluid, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…PN not only improves the computational efficiency but also considers the variation of Laplace pressure. By solving the Hagen‐Poiseuille equation in the resolution at the level of the pore, PN can simulate fluid invasions on the order of a minute, which may require parallel computing lasting for several days for other simulation techniques (Holtzman & Segre, 2015; Hu, Lan, et al., 2019; Primkulov et al., 2021; Zhao et al., 2019), such as VOF, lattice Boltzmann method (Jiang & Tsuji, 2015, 2016; Jiang et al., 2014, 2022; Liu et al., 2015), and computational fluid dynamics (Ferrari et al., 2015; Hu et al., 2017). However, for large‐scale fluid invasion, the computational efficiency needs to be further improved.…”
Section: Introductionmentioning
confidence: 99%